2022
DOI: 10.3390/v14051096
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Hepatitis C in Southern Italy: A Model of HCV Screening and Linkage to Care among Hospitalized Patients at Different Hospital Divisions

Abstract: Background: Free-of-charge HCV screening in some key populations and in 1969–1989 birth cohorts has been funded in Italy as the first step to diagnosing individuals who are infected but asymptomatic. The aim of this study is to evaluate the feasibility of an opportunistic HCV screening and its linkage to care. Methods: A hospital-based HCV screening was conducted as a routine test for in-patients admitted to the Evangelical Hospital Betania of Naples from January 2020 to May 2021. All consecutive in-patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 23 publications
4
20
0
Order By: Relevance
“…Another point raised by our study is the high percentage of subjects with positive anti‐HCV but negative HCV–RNA values (71.7%). This data is in line with other reports, as rates of undetectable HCV–RNA in anti‐HCV positive subjects identified by opportunistic screening programs in recent studies vary between 64% and 82%, 11–14 to be lower in individuals unaware of their status (0%–33%) 8,17,12–14 . Although patients with a sustained virological response (SVR) should not have been included in our study, we cannot exclude that some of them did still participate to this screening program.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another point raised by our study is the high percentage of subjects with positive anti‐HCV but negative HCV–RNA values (71.7%). This data is in line with other reports, as rates of undetectable HCV–RNA in anti‐HCV positive subjects identified by opportunistic screening programs in recent studies vary between 64% and 82%, 11–14 to be lower in individuals unaware of their status (0%–33%) 8,17,12–14 . Although patients with a sustained virological response (SVR) should not have been included in our study, we cannot exclude that some of them did still participate to this screening program.…”
Section: Discussionsupporting
confidence: 91%
“…Results from those studies were comparable, despite potential differences in the target population: "healthy" individuals undergoing anti-COVID-19 vaccination in the first study versus people hospitalized for any reason in the second one. 8,14 Other studies conducted in unselected people (any age) reported prevalence of active HCV infection of 0.5% and 0.7% in hospitalized subjects, 11,12 and of 0.07% in those undergoing anti-SARS-CoV-2 testing or vaccination. 13 Not unexpectedly, taking together all these studies reveal prevalence of viraemic patients lower than that reported in studies conducted before 2019, [15][16][17] TA B L E 3 Main patients' characteristics and screening outcome according to recruitment setting and birth cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the birth cohorts, in line with previous research, we found that more than 70% of viraemic patients were born before 1947 and around 22% between 1948–1968 [ 17 ]. This implies that diagnosis and linkage to care in birth cohorts of subjects with several comorbidities—and frequently with an advanced liver disease—are strictly required, in addition to the mass screening of the 1969–1989 birth cohort of individuals unaware of their infection status, already covered by a dedicated funding to achieve HCV elimination in Italy.…”
Section: Discussionsupporting
confidence: 86%
“…These findings add to recent evidence highlighting that an active HCV case-finding strategy in the hospital setting is an important opportunity to enhance HCV diagnosis and to reduce barriers to HCV cascade care and cure. Rosato et al showed the opportunistic hospital screening in admitted patients with various comorbidities as a feasible strategy to diagnose and subsequently easily link to care the infected patients [ 17 ]. Messina et al reported the efficacy of an innovative model of HCV micro-elimination in a hospital setting through a retrospective analysis of internal databases and recalling patients with positive HCV-Ab [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In countries where this is impossible, usually due to the reluctance of central or local authorities, it is justified to screen patients admitted to hospitals for various reasons, which is able to provide quick diagnosis and start treatment of HCV infection. The legitimacy of such a procedure was confirmed by Rosato et al [ 6 ] on the basis of the results of a program implemented at the Evangelical Hospital Betania of Naples. This program allowed for the detection of 91 infected people among 12,665 tested subjects, 96% of whom underwent treatment and obtained a sustained virologic response.…”
Section: Testing and Linkage To Carementioning
confidence: 87%